Respon Pembaca Terhadap Kumpulan Puisi Hujan Bulan Juni Sepilihan Sajak Karya Sapardi Djoko Damono - Awangdani, Rezky Ayu; Elmustian, Elmustian; Syafrial, Syafrial (UIR PRESS, 2021)
This study describes the reader's response to the ease and interest of students of SMK Negeri 1 Pekanbaru in understanding the elements of physical structure in the 10 poems in the collection of the poetry of Hujan Bulan Juni Sepilih Sajak by Sapardi Djoko Damono, who is one of the most famous writers in Indonesia with his various literary works, through distribution. a questionnaire of 50 students of SMK Negeri 1 Pekanbaru taken purposively. This research is a qualitative research. This research uses descriptive method. Data collection techniques in this study were obtained from questionnaires and interviews as supporters. The data analysis technique in this study begins with the steps, namely running a questionnaire, classifying the results of the response, grouping, discussing, connecting, making results, and drawing conclusions to get a picture of the object under study. Based on the results of data analysis, it was found that 10 poems from the collection of Hujan Bulan Juni Sepilih Sajak by Sapardi Djoko Damono received positive responses from readers, namely as many as 4,922 and negative responses from readers as many as 1,578, so if the two responses were put together, the results were 6,500 responses.